How institutional work by sharing economy organizations and city governments shapes sustainability - Mont, Oksana (Edward Elgar Publishing, 2019)
The sharing economy is a fast-evolving field, but there are gaps in understanding how and why it emerges, evolves and becomes institutionalized. City governments play an important role in shaping the institutional environment of sharing economy organizations (SEOs). However, little is known about the institutional work of SEOs and city governments, and how it can help to leverage the sustainability potential of the sharing economy. This chapter aims to address these gaps by combining conceptual insights from neo-institutional theory with empirical data from five cities: Berlin, London, Malmö, San Francisco and Seoul. The mechanisms of institutional work of SEOs are analyzed using a framework developed by Lawrence and Suddaby and adapted by Zvolska and colleagues, which we modify to reflect the mechanisms of institutional work of city governments. Empirical data sources include case studies of SEOs, field observations and 80 in-depth interviews. Empirical examples illustrate the institutional work of SEOs and city governments. This chapter contributes to neo-institutional theory by testing the framework for institutional work against empirical data from SEOs, third-party actors and five city governments. It contributes to research on the sharing economy by adapting the framework for institutional work to the new agent, city government.